1991
DOI: 10.1021/jo00003a017
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of trifluoromethyl and other perfluoroalkyl compounds with (perfluoroalkyl)trimethylsilanes

Abstract: The preparation of a variety of novel perfluoroalkyl-substituted compounds in high yields using easily prepared (perfluoroalky1)trimethylsilanes (la-c) is described. (Trifluoromethy1)-, (pentafluoroethy1)-, and (heptafluoropropyl)trimethylsilane, la-c, respectively, react readily with carbonyl compounds, such as aldehydes and ketones, by a fluoride-initiated catalytic process. Fluoride-initiated addition of 1 to a carbonyl group generates an oxyanionic species which then further catalyzes the reaction. Even en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
126
0
4

Year Published

1998
1998
2011
2011

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 265 publications
(131 citation statements)
references
References 0 publications
1
126
0
4
Order By: Relevance
“…2,2,2-Trifluoro-1-(4,5-dimethoxy-2-nitrophenyl)ethanol 4 Fa and hydroxy(4,5-dimethoxy-2-nitrophenyl)acetonitrile 4 CNa were prepared by reaction of 4,5-dimethoxy-2-nitrobenzaldehyde with (trifluoromethyl) trimethylsilane [36] and trimethylsilane cyanide, respectively, in THF in 80 and 90 % yield. Condensation of chloroform on 4,5-dimethoxy-2-nitrobenzaldehyde in the presence of 1,…”
Section: Synthesesmentioning
confidence: 99%
“…2,2,2-Trifluoro-1-(4,5-dimethoxy-2-nitrophenyl)ethanol 4 Fa and hydroxy(4,5-dimethoxy-2-nitrophenyl)acetonitrile 4 CNa were prepared by reaction of 4,5-dimethoxy-2-nitrobenzaldehyde with (trifluoromethyl) trimethylsilane [36] and trimethylsilane cyanide, respectively, in THF in 80 and 90 % yield. Condensation of chloroform on 4,5-dimethoxy-2-nitrobenzaldehyde in the presence of 1,…”
Section: Synthesesmentioning
confidence: 99%
“…[17] Importantly, TMSCF 3 can be used as a trifluoromethyl anion source at low temperatures, and the decomposition of the trifluoromethyl anion to difluorocarbene and a fluoride ion at low temperatures was recognized as a side decomposition reaction. [18] Based on this background, we studied the cyclopropanation reaction of alkenes with TMSCF 3 at low temperatures using nonmetallic fluoride sources as initiators. Additionally, we found that TMSCF 3 can be easily activated even at room and/or higher temperatures, and we explored reactions of this reagent with alkenes and even alkynes at 65 8C under iodide-based activation.…”
mentioning
confidence: 99%
“…Solvents were purified by reported methods. [21] [Me 4 N]F, [22] Me 3 SiCF=CF 2 [23] and Me 3 SiC 2 F 5 [24] were synthesised following literature procedures.…”
Section: Methodsmentioning
confidence: 99%